Epidemiological Study of Various Skin Diseases and Prescription Pattern of Drugs in Dermatological OPD in Khammam Region - Kumar, T Praveen; Shivani, S (Indian Journal of Pharmacy Practice)
Background: The study is conducted to identify the epidemiology of various skin diseases in and around Khammam (District Government Hospital, Khammam) and to assess the prescription pattern of drugs in dermatological OPD. Objectives: The main objective is to identify the pattern of drugs used in skin OPD and also to know distribution of clinical types according to age, gender, socio-economic status and disease. Methods: The study was designed to be a prospective observational Study. It was conducted in out-patient department of Dermatology, District headquarters government hospital, Khammam, over a period of 6 months from November 2018 to April 2019 which includes 300 Cases. Patients are randomly enrolled in the study based on inclusion and exclusion criteria. Specially designed Annexure-I (Patient standard data collection form) is used to obtain the data required for the study. Results: In our study, we screened 300 patients out of them 151 (50.3%) were male and 149 (49.7%) were females. It was found that bacterial diseases accounts 43 (14.3%), 59 (19.6%) are fungal diseases, 11 (3.6%) are viral diseases, 85 (28.3%) are parasitic diseases, 45 (34%) are inflammatory skin diseases and 57 (19%) are other category of skin diseases. Conclusion: The major skin diseases identified from our study were scabies, tinea corporis, eczema, acne and urticaria in which male patients were more susceptible. The most common class of drugs prescribed in our hospital includes Antihistamines (23.8%), Antacid (20.9%), Antibiotics (20.8%), Antifungals (8.4%), Antiparasitic (8.3%) and Corticosteroids (5%). The infectious diseases were more common (65%) followed by non-infectious diseases (34%). Public awareness regarding personal hygiene and healthy living is necessary to reduce the burden of skin diseases and for improved quality of life in people especially in rural areas and developing nations.
Keywords: Bacterial Diseases; Dermatology; Prescription Pattern; Personal Hygiene; Scabies; Tinea corporis.